Healthcare personnel exposure to COVID - 19: an observational study on quarantined positive workers - Rubbi, Ivan; Pasquinelli, Gianandrea; Brighenti, Aura; Fanelli, Marcella; Gualandi, Patrizia; Nanni, Eleonora; D'Antoni, Viviana; Fabbri, Cristina (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the study. COVID-19 is characterized by super spread events occurring in communities, e.g., hospitals. To limit virus diffusion among healthcare workers the use of personal protective equipment and screening tests are highly advised; also, isolation of virus positive professionals while monitoring their health condition is recommended. This study aims to assess, in a cohort of COVID-19 positive quarantined healthcare workers, the perceived source of infection and exposure risk as well as the clinical evolution of the disease through a surveillance interview. Methods. A retrospective observational study accounting 896 observations on 93 healthcare professionals tested positive for COVID-19. Data were collected from the Nursing and Technical Directorate of Romagna, Ravenna, Local Health Company, Italy. Results. 99.5% of the positive workers accepted phone interviews with management staff. 2.6% of workers were positive with increasing records in the specialist medical area. Nurses and social health professionals were mostly affected. Patient exposure at a distance <1 m and a contact time > 2 hours was the first cause of positivity. In COVID-19 and territorial emergency departments, the first cause was the contact with colleagues. At the time of the infection, most of the staff wore a surgical mask. Cough, asthenia, fever, anosmia, dysgeusia, and rhinitis were common symptoms. Asymptomatic percentage was about 10%. The self-perceived physical condition was high (>7) and improved during the observation period. Conclusions. The diffusion rate of COVID-19 among healthcare workers is relatively low, probably due to the use of personal protective equipment. The distancing, also among colleagues, is a fundamental measure to reduce the possibility of infection. Symptoms are mild and can be controlled by surveillance measures. Constant contact with the organization is an essential strategy for promoting recovering of workers and reducing the spread of the virus within the healthcare organization.